Integral majorization theorem for invex functions - Khan, Muhammad Adil; Kilicman, Adem; Rehman, Nasir (Hindawi Publishing Corporation, 2014)
We obtain some general inequalities and establish integral inequalities of the majorization type for invex functions. We give applications to relative invex functions.